Whisker-Mediated Touch System in Rodents: From Neuron to Behavior - Adibi, Mehdi (Frontiers in Systems Neuroscience, 2019)
A key question in systems neuroscience is to identify how sensory stimuli are represented in neuronal activity, and how the activity of sensory neurons in turn is ``read out'' by downstream neurons and give rise to behavior. The choice of proper model system to adress these questions, hence, is a crucial step. Over the past decade, the increasingly powerful array of experimental approaches that has become available in non-primate models (e.g. optogenetics and two-photon imaging) has spurred a renewed interest for the use of rodent models in systems neuroscience research. Here we introduce the rodent whisker-mediated touch system as a structurally well-established and well-organized model system which despite its simplicity gives rises to complex behaviors. This system serves as a behaviorally efficient model system; known as nocturnal animals, along with their olfaction, rodents rely on their whisker-mediated touch system to collect information about their surrounding environment. Moreover, this system represents a well-studied circuitry with a somatotopic organization: at every stage of processing, one can identify anatomical and functional topographic maps of whiskers: ``barrelettes'' in the brainstem nuclei, ``barreloids'' in the sensory thalamus, and ``barrels'' in the cortex. This article provides a brief review to the basic anatomy and function of the whisker system in rodents.